1993
DOI: 10.1246/cl.1993.1287
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hydrogen Peroxide and Organic Hydroperoxides in the Reactions of Ozone with Natural Hydrocarbons in Air

Abstract: Reaction of ozone with three kinds of olefins in air was studied. H2O2, CH3OOH, and HOCH2OOH were collected and analyzed with HPLC with a fluorometric detector. Direct reaction of CH2OO with H2O was found to be the source of HOCH2OOH. CH3OOH was formed only from the olefins which have a methyl group. Detailed reaction mechanisms are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…During horizontal turning flights of approximately 10 minutes at each altitude (the flight route is not presented in Fig. 1 because the flight radius was as small as approximately 5 km), air samples were aspirated at 4.0 liters per minute for 10 minutes through a Teflon tube (6 mm ID, 1 m long) by a mist chamber (Hatakeyama et al 1993;Watanabe et al 2016), and H 2 O 2 and HCHO were collected in the collection solution. After 10 minutes of sampling at an altitude of 8000 ft (approximately 2400 m), the helicopter immediately descended to a height of about 5 m over the Toyama Prefectural University campus and dropped the sample (poly ethylene bottle containing the sample solution).…”
Section: Methodsmentioning
confidence: 99%
“…During horizontal turning flights of approximately 10 minutes at each altitude (the flight route is not presented in Fig. 1 because the flight radius was as small as approximately 5 km), air samples were aspirated at 4.0 liters per minute for 10 minutes through a Teflon tube (6 mm ID, 1 m long) by a mist chamber (Hatakeyama et al 1993;Watanabe et al 2016), and H 2 O 2 and HCHO were collected in the collection solution. After 10 minutes of sampling at an altitude of 8000 ft (approximately 2400 m), the helicopter immediately descended to a height of about 5 m over the Toyama Prefectural University campus and dropped the sample (poly ethylene bottle containing the sample solution).…”
Section: Methodsmentioning
confidence: 99%
“…The α-pinene is one of volatile organic compounds (VOCs). In this experiment, liquid-phase α-pinene was evaporated by warm water in an electrical hot water bath and reacted with O 3 in the phytotron (Hatakeyama, 1993). Chen et al (2005) reported that α-pinene caused no visible foliar injury and reduction of biomass in radishes.…”
Section: Exposure Treatmentsmentioning
confidence: 99%
“…Therefore, in this present study, we assumed that α-pinene is not harmful to plants. The concentration of gaseous peroxides in each phytotron was measured by using Pyrex mist chamber method (Hatakeyama et al, 1993;Chen et al, 2010). Solution samples were basically collected three times a day: in the morning, early afternoon and late afternoon.…”
Section: Exposure Treatmentsmentioning
confidence: 99%
“…Peroxides always coexist with O 3 in the air by the reaction of O 3 and volatile organic compounds (VOC). Atmospheric peroxides generally comprise hydrogen peroxide (H 2 O 2 ) and organic peroxides such as methyl hydroperoxide (MHP) and hydroxymethyl hydroperoxide (HMHP) (Hatakeyama et al, 1993;Takami et al, 2003). In fact, combined O 3 and peroxides are much more harmful to some vegetables and other plants than single O 3 (Chen et al, 2005;Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%